Immunisation practices in centres caring for children with perinatally acquired HIV: A call for harmonisation. Issue 46 (4th November 2016) - ,; Menson, Esse N.; Muñoz-Fernández, M. Ángeles; Della Negra, Marinella; Shingadia, Delane; Levy, Jack; Marczynska, Magdalena; Conejo, Pablo Rojo; Klein, Nigel; Ananworanich, Jintanat; Ziegler, John Bernard; Lyall, Hermione; et al.
Abstract: Background: Current national immunisation schedules differ between countries in terms of vaccine formulation, timing of vaccinations and immunisation programme funding and co-ordination. As a result, some HIV infected paediatric population may be left susceptible to vaccine preventable infections. Vaccines used in healthy population should be subjected to high quality ethical research and be explicitly validated for use in children with special vaccination needs such as those infected with HIV. This survey was completed to assess current vaccination practices and attitudes toward vaccination among pediatricians who care for vertically HIV infected children. Methods: An online questionnaire was completed by 46 experts in paediatric HIV-infection from the Paediatric European Network for Treatment of AIDS (PENTA). Data were collected between November 2013 and March 2014. Results: 46 units looking after 2465 patients completed the questionnaire. The majority of units (67%) reported that common childhood immunisation were administered by the family doctor or local health services rather than in the HIV specialist centre. Vaccination histories were mostly incomplete and difficult to obtain for 40% of the studied population. Concerns were reported regarding the use of live attenuated vaccines, such as varicella and rotavirus, and these were less frequently recommended (61% and 28% of the units respectively). Monitoring of vaccine responses was employed in a minority of centres (41%). A range of different assays were used resulting in diverse units of measurement and proposed correlates of protection. Conclusion: Vaccination practices for perinatally HIV-infected children vary a great deal between countries. Efforts should be made to improve communication and documentation of vaccinations in healthcare settings and to harmonise recommendations relating to additional vaccines for HIV infected children and the use of laboratory assays to guide immunisation. This will ultimately improve coverage and vaccine induced immunity in this vulnerable patient group.